Analysis of barriers to blockchain technology adoption in the African agri-food supply chain - Yassine Elkoraichi; Said Elfezazi; Amine Belhadi (Discover Sustainability)
Abstract Blockchain technology is reshaping the agri-food supply chains, providing unique benefits to improve supply chain transparency, traceability, and sustainability. However, blockchain implementation is a challenging task due to the several barriers that come with it. Therefore, this research aims to investigate the major barriers to blockchain technology adoption in the agri-food supply chain within the African context. The paper identified 12 barriers through a literature review and expert opinions. The Decision-Making Trial and Evaluation Laboratory (DEMATEL) approach is used to determine the cause-and-effect relationship among barriers. In light of the results, seven barriers belong to the cause group, and the remaining five barriers fall under the effect group. The analysis shows that the lack of regulation and the lack of infrastructure are the main influencing cause barriers. The study outcome will provide valuable insights for African policymakers to take the necessary steps to overcome these barriers and increase the rate of blockchain adoption in Africa.